Implementation of Religious Extracurricular Activities for Elementary School - Wanda Sabriana Halim; Umu Huzaemah; Nuraiman Nuraiman; Esa Reftilova; Muhammad Taufan; Fauzi Akmal (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2024)
The instilling of religious values ??by teachers in students is not only carried out during religious lesson hours. Teachers can also do this outside of class hours through religious extracurricular activities. The aim of this study is to find out the forms of religious extracurricular activities. This research uses a qualitative method with a case study type (case study). Data sources were taken from twenty informants through direct interviews using a set of interview protocols. The informants involved were selected using purposive sampling techniques. Data sources were taken from twenty informants consisting of school principals, Islamic Religious Education teachers, class teachers, and students in grades IV, V, and VI. All data was then collected using observation, interview and documentation techniques. The results of the analysis show that there are two forms of extracurricular religious activities for elementary school students, namely funeral prayers and tahfidz. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.